Implementasi Pembelajaran berbasis Animasi Powtoon untuk Meningkatkan Hasil Belajar pada Mata Pelajaran PKKR - Anreski, Vanny; Nugraha, Ikhsan Dani (Universitas Negeri Padang, 2023)
One application to create educational animation video media is the Pawtoon application. The animation video is implemented in the light vehicle electrical maintenance subject, after this video is implemented it is seen how the development of the resulting value. The subject of Light Vehicle Electrical Maintenance is a productive subject which is one of the requirements for advancing to the class of SMK students. This study uses quantitative research with experimental methods. This study used a posttest only control design. posttest only control design. From the results of experimental research that has been carried out, it can be concluded that there are significant differences between learning outcomes and the application of pawtoon applications in class XI TKRO SMKN 1 SUMBAR.